2020
DOI: 10.1155/2020/3235429
|View full text |Cite
|
Sign up to set email alerts
|

A Regret Theory-Based Decision-Making Method for Urban Rail Transit in Emergency Response of Rainstorm Disaster

Abstract: The decision-making for urban rail transit emergency events takes an important role in both reducing the losses caused by disasters and ensuring the safety of passengers. For the rainstorm emergency decision-making without certain scenario prediction information, considering the characteristic that the predisaster prevention measures will influence the effect of in-process countermeasures, this paper aimed to analyze the whole process scenarios for the occurrence, evolution, and development of rainstorm disast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…If θ < 0.5, the decisionmaker's risk preference is passive and pessimistic. Also, when θ � 0.5, it is neutral, and equation ( 9) can be simplified as equation (8). Since the satisfaction index has advantages on objectively describing the decision-maker's expected satisfactory degree of psychological reference, it has been widely used in the research of multiattribute decision-making problems.…”
Section: Dynamic Adjustment Methods Based On the Satisfaction Information Updatingmentioning
confidence: 99%
See 1 more Smart Citation
“…If θ < 0.5, the decisionmaker's risk preference is passive and pessimistic. Also, when θ � 0.5, it is neutral, and equation ( 9) can be simplified as equation (8). Since the satisfaction index has advantages on objectively describing the decision-maker's expected satisfactory degree of psychological reference, it has been widely used in the research of multiattribute decision-making problems.…”
Section: Dynamic Adjustment Methods Based On the Satisfaction Information Updatingmentioning
confidence: 99%
“…Taking the EDM as a problem of risk analysis, Liu et al and Wang et al presented an EDM approach considering the DMs' decision behaviors based on prospect theory [6,7]. Wang et al focused on regret theory, which means that the DMs tend to generate an expected regret for decision based on past experiences and established a decision-making method for emergency response of rainstorm disaster [8]. Xu et al considered DMs' trust relations and preference risks and developed consensus-based EDM approach [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several researchers proposed regret theory-based methods to solve decision-making problems. For example, the authors in [24] proposed a regret theory-based decision-making method in order to solve problems of urban transportation systems stressed by rainstorms in Tianjin; this method could improve the reliability and risk-response capability of local public transportation service.…”
Section: Overview Of Regret and Rejoice In Mcdmmentioning
confidence: 99%
“…For a mine EDM problem, Liang et al [ 26 ] proposed a multi-granularity proportional hesitant fuzzy linguistic TODIM method. Wang et al [ 61 ] suggested a regret theory-based EDM model for the emergency response to different rainstorm disaster scenarios. Thereafter, Wang and Day [ 62 ] applied the AHP method to explore the selection and prioritization of major decision making factors for typhoon disaster preparedness and emergency response.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, because of the lack of decision information and the uncertainty and complexity of emergencies, it is difficult to cope with emergencies through conventional response measures [ 71 ]. Consequently, the emergency decision making (EDM) problem has recently attracted increasing attention from scholars and governments [ 2 , 9 , 13 , 22 , 25 , 61 , 65 ]. Multiple criteria decision making (MCDM) techniques, which support decision makers (DMs) in choosing the best option from several alternatives based on multiple and often conflicting criteria, are considered effective means to determine the best solution in EDM problems [ 4 , 8 , 36 , 52 ].…”
Section: Introductionmentioning
confidence: 99%